Preliminary report on the Cicadomorpha (Hemiptera) fauna of Kemaliye (Erzincan Province, East Turkey) - Demir, Emine (Acta entomologica slovenica (Ljubljana), 2016)
Cicadomorpha specimens collected in the years 2006 and 2007 in the Kemaliye (Erzincan province) in east Turkey were examined. 63 species belonging to 7 families were found: 4 species belong to the family Cicadidae, 1 to Tibicinidae, 1 to Cercopidae, 6 Aphrophoridae, 1 to Membracidae, 1 Ulopidae and 49 species to Cicadellidae. Distribution of these species in Turkey and their host plants are given along with their locality records. 52 species records are new to the Kemaliye district, 32 new to Erzincan province and 8 species records are new to eastern Turkey.
Keywords: Cicadomorpha; fauna; Hemiptera; Turčija; Turkey; žuželke